Town centre management: outlook from Portugal - Guimarães, Pedro (2019)
In the last two decades, the Portuguese Government has responded to the decline of centres of commerce. In this paper, we analyse the three different experiences of town centre management (TCM) schemes developed in Portugal since the turn of the millennium. The first two stages were developed using public sector initiatives and their impacts were limited. The third stage is still under way and is composed of private projects created by local business owners. Taking Lisbon as a case study for this third stage we conclude that these projects have become a pro-active means of intervention in Portuguese town centres.